The Effect of Walking Exercise on Blood Pressure in The Elderly With Hypertension in Mulyoharjo Community Health Center Pemalang - Yulisa, Dinda Kartika; Mukarromah, Siti Baitul (Public Health Perspective Journal, 2018)
The prevalence of hypertension in Indonesia at the age of 18 is 34.1%, lower than that of in Central Java, which is 38.4%. One of the causes of hypertension is lack of physical activities. One of the physical activities that can reduce hypertension is walking. This study aims at determining the effect of walking exercise on blood pressure in the elderly with hypertension of obesity nutritional status. This study used a control group time series design involving 10 samples consisting of 5 respondents with hypertension of normal nutritional status and 5 respondents with hypertension of obesity nutritional status. The results of this study showed that the blood pressure of the elderly with hypertension before doing walking exercise was 152.20 / 95.80 mmHg and after doing walking exercise was 147.60 / 93.60 mmHg in average. Walking exercise decreases blood pressure in the elderly with hypertension of obesity nutritional status. The results of the study can be regarded as a consideration in taking community health program policy for the elderly with hypertension on the effectiveness of walking exercise as one of the means in reducing blood pressure.